2003
DOI: 10.1029/2003gl017415
|View full text |Cite
|
Sign up to set email alerts
|

First evidence for the detection of natural surface films by the QuikSCAT scatterometer

Abstract: For the first time it is demonstrated that with the QuikSCAT scatterometer it is possible to detect natural surface films resulting from enhanced biological activity in the ocean. It is shown for two regions in the Norwegian and Baltic Sea that areas of strongly reduced Normalized Radar Cross Section (NRCS) are associated with areas of enhanced chlorophyll‐a concentration as evidenced by quasi‐simultaneously acquired SeaWiFS data. This result has two implications. Firstly, it opens up the possibility to map gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…As for oceanic rain, it is foreseen that one can build a slick climatology within different chosen regions. These climatologies could then be profitably compared with the regions of reduced backscatter observed in scatterometer data which have been associated with natural surface slicks by comparison with ocean color data [ Lin et al , 2003; Hashizume and Liu , 2004].…”
Section: Resultsmentioning
confidence: 99%
“…As for oceanic rain, it is foreseen that one can build a slick climatology within different chosen regions. These climatologies could then be profitably compared with the regions of reduced backscatter observed in scatterometer data which have been associated with natural surface slicks by comparison with ocean color data [ Lin et al , 2003; Hashizume and Liu , 2004].…”
Section: Resultsmentioning
confidence: 99%
“…The relations between dW and log 10 (CHL) are almost linear, and that dW increases from ∼−1 m s −1 to ∼0.5 m s −1 as CHL increases from ∼0.1 mg m −3 to ∼3 mg m −3 . This ∼1.5 m s −1 reduction of scatterometer wind is quantitatively reasonable relative to the previous experimental studies although it is much smaller than the amplitude of dW observed from instantaneous comparison by Lin et al [2003]. For instance, Feindt 's [1985] laboratory wind wave tank experiments with X‐band (9.8 GHz) scatterometer [see also Alpers and Hühnerfuss , 1989, Figure 5] shows that artificial surface film causes ∼7 dB backscatter reduction at 7 m s −1 wind speed, which corresponds to ∼3 m s −1 wind speed underestimation.…”
Section: Resultsmentioning
confidence: 99%
“…There are also some airborne Ku‐band scatterometer experiment studies [e.g., Hühnerfuss et al , 1978; Singh et al , 1986; Gade et al , 1998]. There have been no observations of such effect on spacebased scatterometers in open ocean until the recent study by Lin et al [2003]. They showed that backscatter reduction on QuikSCAT occurred near the chlorophyll‐a‐rich area in the northern North Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…), Chapron et al (2000) considered that the shape of the sea surface slope probability distribution function can partially explain such discrepancies. In particular, Lin et al (2003) have showed that anomalous backscatter regions observed by the Quick scatterometer (QuikSCAT) often correspond to such phenomena locations as recalled by Mitchum et al (2004). Anderson et al (2002) also pointed out the limitations they ran into as a result of the lack of absolute calibration of TOPEX 0 .…”
Section: Benefits Expected From the Absolute Calibration Of Altimementioning
confidence: 95%